Dose proportionality and comparison of single and multiple dose pharmacokinetics of fexofenadine (MDL 16 455) and its enantiomers in healthy male volunteers - Robbins, Doris K.; Castles, Mark A.; Pack, David J.; Bhargava, Vijay O.; Weir, Scott J. (Biopharmaceutics & drug disposition, 1998)
The pharmacokinetics and dose proportionality of fexofenadine, a new non‐sedating antihistamine, and its enantiomers were characterized after single and multiple‐dose administration of its hydrochloride salt. A total of 24 healthy male volunteers (31±8 years) received oral doses of 20, 60, 120 and 240 mg fexofenadine HCl in a randomized, complete four‐period cross‐over design. Subjects received a single oral dose on day 1, and multiple oral doses every 12 h on day 3 through the morning on day 7. Treatments were separated by a 14‐day washout period. Serial blood and urine samples were collected for up to 48 h following the first and last doses of fexofenadine HCl. Fexofenadine and its R(+) and S(−) enantiomers were analysed in plasma and urine by validated HPLC methods. Fexofenadine pharmacokinetics were linear across the 20–120 mg dose range, but a small disproportionate increase in area under the plasma concentration–time curve (AUC) (<25%) was observed following the 240 mg dose. Single‐dose pharmacokinetics of fexofenadine were predictive of steady‐state pharmacokinetics. Urinary elimination of fexofenadine played a minor role (10%) in the disposition of this drug. A 63:37 steady‐state ratio of R(+) and S(−) fexofenadine was observed in plasma. This ratio was essentially constant across time and dose. R(+) and S(−) fexofenadine were eliminated into urine in equal rates and quantities. All doses of fexofenadine HCl were well tolerated after single and multiple‐dose administration. © 1998 John Wiley & Sons, Ltd.